Anaemia among clinically well under-fives attending a community health centre in Venda, Limpopo Province - Heckman, James (2010)
BACKGROUND: Anaemia has been reported to affect 20 – 75% of children in South Africa. The range suggests the effects that geography, health, and socio-economic status can have on the observed prevalence of anaemia within a specific community. Our objective was to investigate the prevalence of anaemia in children aged under 5 presenting for well-child examinations at a community health centre in Thohoyandou, Limpopo Province. DESIGN: A cross-sectional observational study was carried out in June and July 2007. Caregivers participated in a brief interview where demographic, health and nutritional information was collected. A blood sample was collected from each child, and haemoglobin levels were assessed with a point-of-care haemoglobin testing system. Anaemia was defined as having a haemoglobin value <2 standard deviations below age-altitude adjusted normal values. RESULTS: Three-quarters (39/52 – 75%) of children were anaemic. Girls were significantly more likely to be anaemic than boys (20/20 v. 19/32 respectively; p=0.001). Anaemic children were significantly less likely to be underweight compared with their peers (32/38 v. 5/12 respectively; p=0.007). There was no significant association between anaemia and infection with Helicobacter pylori (p=0.729), intestinal helminths (p=1.000) or food insecurity (p=0.515). CONCLUSION: We found a striking prevalence of anaemia among clinically well children <5 years old in Thohoyandou, Limpopo Province. The rates of anaemia were higher than those found in previous studies conducted in similar settings in South Africa. Future work should focus on aetiologies and interventions.